Transformational Leadership Among Government School Principals and Its Relationship to Teachers' Professional Compatibility in The Governorate of South Al-Sharqiyah in The Sultanate of Oman - Al-Rasbi, Tariq Juma; Al-Dhuhli, Rabia Al-Mur; Al-Habsi, Radhiya Sulaiman; Al-Thani, Yaqoob Salim (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of transformational leadership practice among public school principals and its relationship to the professional adjustment of teachers in the South Al-Sharqiyah Governorate in the Sultanate of Oman. It followed the descriptive, correlational approach. It used a questionnaire, and after ensuring its validity and reliability, it was applied to (381) male and female teachers, The study found that the degree of public school principals’ practice of transformational leadership was high in the overall score and in all dimensions. It also revealed that there were no statistically significant differences in the average teachers’ estimates of the degree of practice of transformational leadership among public school principals due to the variables of years of experience and job level, It concluded that the level of professional compatibility among public school teachers was high, in the overall score and in all dimensions. It revealed that there were no statistically significant differences between the averages of teachers’ estimates of the level of professional compatibility among teachers in public schools due to the variables: years of experience, and the presence of statistically significant differences due to the dimension of job level in all dimensions and the total score with the exception of compatibility with work colleagues, and the differences came in favor of the first teacher. It revealed that there is a positive and statistically significant correlation between public school principals’ practice of transformational leadership and teachers’ professional compatibility.
Keywords: transformational leadership; professional compatibility for teachers; South Al-Sharqiyah Governorate; Oman